Penerapan Gamifikasi untuk Meningkatkan Hasil Belajar Materi Indahnya Keberagaman Ritual dan Kepercayaan Kelas XI SMA Negeri 1 Ampel - Sujiono, Sujiono (Universitas Nusantara PGRI Kediri, 2026)
The study aims to analyze the application of gamification in improving the learning outcomes of class XI students on the subject of The Beauty of Ritual and Belief Diversity. The type of classroom action research. The location of the research was SMAN 1 Ampel Boyolali, Central Java. The subjects in the study were 17 class XI students of SMAN 1 Ampel Boyolali and teachers of Buddhist Religious Education and Character Building. The sampling technique used a purposive procedure. Data collection techniques through observation, interviews, documents, tests. Data validity used triangulation and key informant review. This study used triangulation, namely source triangulation and method triangulation. Data analysis used in this study was descriptive analytical techniques and critical analysis techniques. The results of the study showed that the application of gamification effectively improved student learning outcomes on the subject of The Beauty of Ritual and Belief Diversity. Before the application of gamification, an average score of 72.53 was obtained. Cycle 1 learning by applying gamification. The results of cycle 1's average score were 80.18. Cycle 1 learning experienced an average increase of 7.65 compared to pre-cycle. The average value of cycle 2 was 88.12. The increase in learning outcomes in cycle 2 was 7.94.